Improved Drought Stress Response in Alfalfa Plants Nodulated by an IAA Over-producing Rhizobium Strain - Defez, Roberto; Andreozzi, Anna; Dickinson, Michael; Charlton, Adrian; Tadini, Luca; Pesaresi, Paolo; Bianco, Carmen (Frontiers in Microbiology, 2017)
The drought-stress response in plant involves the cross-talk between absisic acid (ABA) and other phytohormones, such as jasmonates and ethylene. The auxin indole-3-acetic acid (IAA) plays an integral part in plant adaptation to drought stress. Investigation was made on to see how the main auxin IAA interacted with other plant hormones under water stress, applied through two different growth conditions (solid and hydroponic). Medicago sativa plants nodulated by the Ensifer meliloti wild type 1021 (Ms-1021) and its IAA-overproducing RD64 derivative strains (Ms-RD64) were subjected to drought stress, comparing and their response compared. The response of Medicago sativa plants nodulated by the Ensifer meliloti IAA-overproducing RD64 strain (Ms-RD64) to drought stress was evaluated and compared to that of plants nodulated by the wild type 1021 strain (Ms-1021). When the expression of nifH gene and the activity of the nitrogenase enzyme were measured after stress treatments, Ms-RD64 plants recorded a significantly weaker damage. These results were correlated with a lower biomass reduction, and a higher Rubisco protein level measured for the Ms-RD64-stressed plants as compared to the Ms-1021-stressed ones. It has been verified that the enhanced stress response observed for Ms-RD64-stressed plants was related to the production of greater amount of low-molecular-weight osmolytes, such as proline and pinitol, measured in these plants. For the Ms-RD64 plants the immunoblotting analysis of thylakoid membrane proteins showed that some of the photosystem proteins increased after the stress. An increased non-photochemical quenching after the stress was also observed for these plants. The reduced wilting signs observed for these plants were also connected to the significant down-regulation of the MtAA03 gene involved in the ABA biosynthesis, and with the unchanged expression of the two genes (Mt-2g006330 and Mt-8g095330) of ABA signaling. When the expression level of the ethylene-signaling genes was evaluated by qPCR analysis no significant alteration of the key positive regulators was recorded for Ms-RD64-stressed plants. No significant alteration was recorded for the key positive regulators of the ethylene signaling for Ms-RD64-stressed plants when the qPCR analysis of the ethylene-signaling genes and the evaluation of the ethylene produced were carried out after the water stress, and,